2022
DOI: 10.1007/s11356-022-21453-x
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Moringa oleifera Lam. leaf extract against oxidative stress, inflammation, depression, and apoptosis in a mouse model of hepatic encephalopathy

Abstract: The present study aimed to assess the antioxidative, anti-in ammatory, antiapoptotic, and antidepression impacts of Moringa oleifera Lam. leaf ethanolic extract (MOLE) in the hippocampus and cerebral cortex of CCl 4 -induced mouse model of hepatic encephalopathy. High-performance liquid chromatography was used to detect marker compounds; rutin and β-sitosterol. Animals were divided into four groups; vehicle group, CCl 4 treated group, MOLE treated group, and (CCl 4 + MOLE) group treated with MOLE for 14 days b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
(55 reference statements)
1
2
0
Order By: Relevance
“…These results align with previous research; significant antiepileptic and anxiolytic effects were seen with Aqueous Extract M. oleifera (250, 375, and 500 mg/kg, i. p.) [8]. Mahmoud, M. S, et al, also reported M. oleifera leaf extract attenuated CCl4-induced anxiety and behavioral changes such as depression [23].…”
Section: Effect Of Mow On Behavior Abnormalitiessupporting
confidence: 92%
“…These results align with previous research; significant antiepileptic and anxiolytic effects were seen with Aqueous Extract M. oleifera (250, 375, and 500 mg/kg, i. p.) [8]. Mahmoud, M. S, et al, also reported M. oleifera leaf extract attenuated CCl4-induced anxiety and behavioral changes such as depression [23].…”
Section: Effect Of Mow On Behavior Abnormalitiessupporting
confidence: 92%
“…Consequently, this dual effect translated into a reduction in myocardial infarct size and cell apoptosis, underscoring the role of BS as a cardioprotective agent [36]. These findings suggest that BS exerts anti-apoptotic effects in inflammatory states [37].…”
Section: Discussionmentioning
confidence: 82%
“…One study showed that in a model of myocardial ischemia-reperfusion injury, BS upregulated the expression of Bcl-2 and downregulated the expression of caspase-3, which reduced myocardial infarct size and cells apoptosis, playing a role of cardioprotective [33]. Thus, BS exert anti-apoptotic effects in in ammatory states [34].…”
Section: Discussionmentioning
confidence: 99%